Prevalence of Diseases of Otorhinolaryngology Among Immigrant Medical Students in Puducherry - A, Valarmathi.; Siddapur, Geetha Kishan; Venkataramanan, Venkataramanan; S, Ganesh.; Paul. R, Merwin; PM, Abilash (Journal of Neonatal Surgery, 2025)
Introduction Migration can be defined as an extended stay in a cultural environment that is different from the native one. This study focuses on understanding the relationship between health and migration among medical students in Puducherry. It investigates how migrant students may be affected by migration in terms of commonly encountered otorhinolaryngology (ear, nose, and throat) diseases such as rhinitis, sinusitis, hearing loss and tonsillitis in migrant students. Materials and methods A cross-sectional study involving 165 medical students from various regions of India was carried out in a tertiary health centre at Puducherry. A questionnaire including sociodemographic details and otorhinolaryngology related symptoms was used to gather data. Results A study conducted on 165 immigrant medical students showed a significant association between the causation of otorhinolaryngological diseases and migration factors such as exposure to allergens (p=0.002). duration of stay (p=0.015), psychological stress (p<0.001), and living conditions (p=0.045). The most prevalent otorhinolaryngological condition was allergic rhinitis (35.2%), followed by laryngopharyngeal reflux disease (25.5%), sinusitis (21.8%), tonsillitis (17.0%), and chronic otitis media (14.5%). Noise-induced hearing loss was reported in (7.3%) of participants. Conclusion In our study we were able to demonstrate the corelation between causation of the disease and the geographical change and proves that migration has an impact on developing ENT diseases